A Tannakian context for Galois theory - Dubuc, Eduardo Julio (2013)
Strong similarities have been long observed between the Galois (Categories Galoisiennes) and the Tannaka (Categories Tannakiennes) theories of representation of groups. In this paper we construct an explicit (neutral) Tannakian context for the Galois theory of atomic topoi, and prove the equivalence between its fundamental theorems. Since the theorem is known for the Galois context, this yields, in particular, a proof of the fundamental (recognition) theorem for a new Tannakian context. This example is diﬀerent from the additive cases or their generalization, where the theorem is known to hold, and where the unit of the tensor product is always an object of ﬁnite presentation, which is not the case in our context